Prevention Efforts of Young People Against Radicalism in Social Media According to The Conflict Theory of Lewis A. Coser - Ranubaya, Fransesco Agnes; Endi, Yohanes (International Journal of Indonesian Philosophy & Theology, 2024)
Young people are often vulnerable to radicalism that spreads through social media. This study uses library research to explore Lewis A. Coser's Conflict Theory and how radicalism impacts young people online. This study seeks to understand the adverse impact of radicalism on young people and offer strategies to overcome its negative influence. The method used is a literature analysis to understand the relationship between radicalism and social media. The aim is to identify ways to avoid the spread of radicalism among young people and to propose preventive measures. Young people have an important role to play in countering radicalism. Some of the steps that can be taken include improving digital literacy so that they can filter the information they receive, promoting understanding of global issues to prevent extremism, and practicing the principles of Pancasila, particularly Bhinneka Tunggal Ika, to strengthen their sense of nationalism and diversity. This research underscores the importance of the media's contribution to providing positive information that helps steer young people away from radicalism. In addition, this research shows that preventive action from young people is crucial in maintaining unity and preventing social conflicts that may arise due to radicalism. Hopefully, the younger generation can become effective agents of change in keeping Indonesia plural and multicultural.